On ethics and literature: "La ética de la crueldad" (2012), an essay by José Ovejero - Pujante Segura, Carmen María (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Departing from the pairing between literature and philosophy we propose an analysis, an interpretation and an interview with the writer José Ovejero. We delve into his work La ética de la crueldad, which was published in 2012 when he won the Premio Anagrama de Ensayo (Anagrama Essay Award). The new pairing proposed by the title, almost an oxymoron, will be the subject of a brief review of other traditional and problematic associations such as ethics and aesthetics, essay and literature, avoidance and transgression, or politics and education.